x²=(x-9)²+(x-8)²
x²=(x²-9²)+(x²-8²)
x²=x²-9²+x²-8²
x²=x∧4(elevado a la 4)-81-64
x²=x∧4-145
-x∧4+x²=-145
-x²=-145
-x=√-145 (puede dejarlo hasta aqui)
(-1)-x=-12.04(-1) (apoximadamente)
x=12.04
" Life is not a problem to be solved but a reality to be experienced! "
© Copyright 2013 - 2025 KUDO.TIPS - All rights reserved.
x²=(x-9)²+(x-8)²
x²=(x²-9²)+(x²-8²)
x²=x²-9²+x²-8²
x²=x∧4(elevado a la 4)-81-64
x²=x∧4-145
-x∧4+x²=-145
-x²=-145
-x=√-145 (puede dejarlo hasta aqui)
(-1)-x=-12.04(-1) (apoximadamente)
x=12.04